A reverse auction algorithm for carrier allocation in femtocells for multimedia applications. (2016) - Gao, Zhibin; Chiang, Hua-Pei; Huang, Lianfen; Yuan, Yannan; Dai, Huaiyu; Huang, Yueh-Min
An efficient carrier allocation algorithm is important for self-organised networks (SONs). SON can significantly improve network performance and user experience which greatly help relieve the heavy loading of the current multimedia applications for mobile environments. This paper proposes a distributed algorithm for carrier allocation using a reverse auction algorithm, wherein the original cells affected by newly added cells self-organise into auction groups to facilitate new carrier allocation. The computational overhead required to adapt to topology changes can be significantly reduced compared with the conventional topology-based approaches that ignore prior assignments. The number of original cells affected by the reallocation is as small as possible in the reverse auction algorithm while optimising carrier allocation. We investigate the algorithm performance in various scenarios. Our results indicate that the reverse auction algorithm exhibits significant advantages compared with traditional approaches, especially in highly dynamic networks where frequent resource re-allocation is needed.